Inspirational Leadership and Innovative Communication in Sustainable Organizations: A Mediating Role of Mutual Trust - Muhammad Toseef; Muhammad Toseef; Alina Kiran; Sufan Zhuo; Mahad Jahangir; Sidra Riaz; Zong Wei; Zong Wei; Tauqir Ahmad Ghauri; Irfan Ullah; Suraya Binti Ahmad (Frontiers in Psychology, 2022)
The possibility of accomplishing sustainable objectives is largely connected to the management and flourishing of an organizational system which keeps human capital engaged and committed. Our study investigated the association of inspirational leadership and innovative communication with employee engagement and commitment under the lens of leader member exchange theory. Specifically, we emphasized the mediating role of mutual trust in connection to social sustainability facets. A survey of data from employees in the manufacturing sector of Yunnan, China was utilized to test the hypothesized model. The study findings reported a significant association and came to the conclusion that a leader’s inspirational behavior coupled with innovative communication is a significant predictor of engagement and commitment in socially sustainable organizations. Moreover, mutual trust significantly mediated the relationship of innovative communication and inspirational leadership with employee engagement and commitment reaching the social perspective of sustainability. The current study added to the literature of sustainable organization by pointing out the social dimensions of sustainability.